SYSTEMATIC LITERATURE REVIEW: DEVELOPMENT OF ADOLESCENT SELF-CONTROL - Sinta Afiatul Jannah; Siti Sofa Nurjanah; Sunenti Sunenti; Vini Indriyani Al-Afsy; Yulia Nur’aini (Universitas Pendidikan Indonesia, 2023)
Many students experience problems with adolescent self-control that arise. The problems that arise are related to adolescent self-control in acting. Therefore the importance of developing research on self-control in guidance and counselling to improve students' quality of life in facing their future, as well as study material for guidance and counselling practitioners in efforts to develop adolescents. Self-control is an effort or individual ability to regulate, guide, and direct all forms of action in order to lead to positive action. With this self-control, the individual forms emotional control within himself. This article aims to analyze the development of self-control research in guidance and counselling. The method used in writing this article is a systematic literature review by doing a literature search from international journals and national journals. The result of this analysis is that the development of research on adolescent self-control has been carried out and applied a lot. With self-control, adolescents have boundaries that guard them in acting, being emotional, and developing cognition, which impacts avoiding various adolescent deviations.